The Listening Ability of the Fifth Semester Students of the English Department of Widya Mandala Surabaya Catholic University - Fonny Nawa (Magister Scientiae, 2008)
The study under report is a documentary analysis. The subjects are the Academic Year 2005 students of EESP of WMSCU. The writer used the students’ scores along with the test the items as her data. She used descriptive statistics in analyzing the subjects scores after grading the subjects based on their scores. Next, she classified the test items into 8 sub-skills, and analyzed the test items. The findings of the students’ scores analysis show that only 13 (25%) students got A, B+, B, C+, and C, whereas 39 (75%) students got D and E. It can be concluded that as a group the students’ listening ability is poor.